Design of Suction-Type Tactile Presentation Mechanism to Be Embedded in HMD - Kameoka, Takayuki; Kajimoto, Hiroyuki (Frontiers in Virtual Reality, 2022)
To enrich the virtual reality experience and improve realism, many studies have proposed embedding tactile devices into head-mounted displays (HMDs). However, although thermal and vibrotactile cues have become commonplace, presentation of the constant pressure necessary for softness expression remains relatively rare. In this study, we propose a suction-type tactile presentation method that addresses this issue. Through subjective evaluation and simulation using the finite element method, we verified that the proposed suction-type tactile presentation method is suitable for use with HMDs and that by increasing the number and density of the suction holes, a stronger tactile sensation can be created.